Integrative Interventions for Men with Concurrent Substance Misuse and Trauma: Roles for Mindfulness and Masculinities - Foster, Durwin B.; Kelly, Mary Theresa (Canadian Journal of Counselling and Psychotherapy, 2012)
Men experience higher lifetime trauma rates than women, and they use and misuse substances at rates far exceeding women. Men are also reported to experience significantly higher lifetime rates of comorbid posttraumatic stress disorder (PTSD) and substance use disorder (SUD) than women. Although there is agreement in the clinical field of trauma and substance abuse that integrated treatment programs are critical, relapse rates and treatment dropout rates remain relatively high despite the high standards in these programs. Most integrated treatment approaches for co-occurring disorders are based on cognitive-behavioural frameworks that emphasize coping skills and replacing maladaptive cognitions. We address two major gaps in these standard-of-care approaches. First, we examine the context of gender; most programs do not address gender constructs or provide gender-specific materials, and many programs were initially developed for women only. Second, we address the growing evidence for utilizing mindfulness and acceptance components in integrative interventions for men.